2003
DOI: 10.1039/b211660j
|View full text |Cite
|
Sign up to set email alerts
|

Neoglycoconjugates from synthetic tetra- and hexasaccharides that mimic the terminus of the O-PS of Vibrio cholerae O:1, serotype Inaba

Abstract: A glycosyl acceptor and a glycosyl donor having the N-3-deoxy-L-glycero-tetronic acid side chain already attached have been prepared and used for the synthesis of the di-through to the hexasaccharide that mimic the upsteam terminus of the O-specific polysaccharide of Vibrio cholerae O:1, serotype Inaba. The target tetra- and the hexasaccharide, which were obtained in the form of 5-methoxycarbonylpentyl glycosides, were linked to BSA using squaric acid diester chemistry. The conjugation reactions were monitored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 23 publications
0
18
1
Order By: Relevance
“…Our previous syntheses [11,[18][19][20][21][22] of higher oligosaccharides in the Vibrio cholerae O:1 series had their shortcomings due to either instability of protecting groups, lack of stereoselectivity of glycosylation reactions, or separation problems involved. Also, losses resulting from multiple chemical manipulations with high oligosaccharides we experienced during some previous approaches suggested that, rather than a stepwise approach, a suitable block wise strategy using fully functionalized intermediates as building blocks should be pursued.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous syntheses [11,[18][19][20][21][22] of higher oligosaccharides in the Vibrio cholerae O:1 series had their shortcomings due to either instability of protecting groups, lack of stereoselectivity of glycosylation reactions, or separation problems involved. Also, losses resulting from multiple chemical manipulations with high oligosaccharides we experienced during some previous approaches suggested that, rather than a stepwise approach, a suitable block wise strategy using fully functionalized intermediates as building blocks should be pursued.…”
Section: Resultsmentioning
confidence: 99%
“…To minimize waste of the precious oligosaccharides, conjugations described here were performed at a considerably lower initial hapten-carrier ratio (20:1) than in our earlier work. [29][30][31] The expected slower reaction rate due to conducting the conjugation under these conditions 32 was fully compensated for by running conjugations at a higher concentration only in the case of hapten 84 (Table 3). We have no other explanation for the much slower rate of conjugation with haptens 2, 12, and 35, other than, as we pointed out previously, 29 that we may not be aware of some parameters that affect conjugation.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly (Fig. 1A), condensation (23) of the glycosyl acceptor 5 and glycosyl donor 4, prepared from the corresponding amine (7) and 2,4-O-benzylidene-3-deoxy-L-glycero-tetronic acid (24,28), gave the fully protected disaccharide 6. Partial deprotection by Zemplén deacetylation afforded alcohol 7, which was used as a glycosyl acceptor in the next coupling with 4 to extend the oligosaccharide chain and obtain the trisaccharide 8.…”
Section: Methodsmentioning
confidence: 99%
“…Immunogens 1a to 3c were prepared by linking the chemically synthesized di-, tetra-, and hexasaccharide fragments of the O-SP of V. cholerae O1 serotype Inaba to BSA by using squaric acid chemistry (20,36,38). The oligosaccharides were assembled in a stepwise manner (28) (Fig. 1) from the monosaccharide glycosyl donor 4 and the monosaccharide glycosyl acceptor 5.…”
Section: Methodsmentioning
confidence: 99%